37.9k views
5 votes
3x+4)2−(x−10)2 .

Escolha uma opção:
a. 10x2−4x+116
b. 8x2−4x−84
c. 8x2+44x−84
d. 8x2−44x−84
e. 8x2+116

User Disnami
by
5.5k points

1 Answer

1 vote

Given:

Expression is


(3x+4)^2-(x-10)^2

To find:

The simplified form of the given expression.

Solution:

We have,


(3x+4)^2-(x-10)^2

Using
(a+b)^2=a^2+2ab+b^2 and
(a-b)^2=a^2-2ab+b^2, we get


=(3x)^2+2(3x)(4)+(4)^2-[(x)^2-2(x)(10)+(10)^2]


=9x^2+24x+16-[x^2-20x+100]


=9x^2+24x+16-x^2+20x-100

On combining like term, we get


=(9x^2-x^2)+(24x+20x)+(16-100)


=8x^2+44x+(-84)


=8x^2+44x-84

Therefore, the correct option is c.

User ChristofferH
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.